Phylogeny and evolution of Lasiopodomys in subfamily Arvivolinae based on mitochondrial genomics - Shi, Luye (PeerJ, 2021)
The species of Lasiopodomys Lataste 1887 with their related genera remains undetermined owing to inconsistent morphological characteristics and molecular phylogeny. To investigate the phylogenetic relationship and speciation among species of the genus Lasiopodomys, we sequenced and annotated the whole mitochondrial genomes of three individual species, namely Lasiopodomys brandtii Radde 1861, L. mandarinus Milne-Edwards 1871, and Neodon (Lasiopodomys) fuscus Büchner 1889. The nucleotide sequences of the circular mitogenomes were identical for each individual species of L. brandtii, L. mandarinus, and N. fuscus. Each species contained 13 protein-coding genes (PCGs), 22 transfer RNAs, and 2 ribosomal RNAs, with mitochondrial genome lengths of 16,557 bp, 16,562 bp, and 16,324 bp, respectively. The mitogenomes and PCGs showed positive AT skew and negative GC skew. Mitogenomic phylogenetic analyses suggested that L. brandtii, L. mandarinus, and L. gregalis Pallas 1779 belong to the genus Lasiopodomys, whereas N. fuscus belongs to the genus Neodon grouped with N. irene. Lasiopodomys showed the closest relationship with Microtus fortis Büchner 1889 and M. kikuchii Kuroda 1920, which are considered as the paraphyletic species of genera Microtus. T(MRCA) and niche model analysis revealed that Lasiopodomys may have first appeared during the early Pleistocene epoch. Further, L. gregalis separated from others over 1.53 million years ago (Ma) and then diverged into L. brandtii and L. mandarinus 0.76 Ma. The relative contribution of climatic fluctuations to speciation and selection in this group requires further research.